The entrepreneurial rent: the value of and compensation for entrepreneurship. Issue 1 (10th April 2017) - Henrekson, Magnus; Stenkula, Mikael
Abstract : Purpose: The purpose of this paper is to show that entrepreneurship can be fruitfully analyzed by positing that entrepreneurs are searching for rates of return exceeding the risk-adjusted market rate of return, i.e., they try to create or discover economic rents. Design/methodology/approach: A conceptual paper trying to bridge the gap between neoclassical economics and the entrepreneurship field by seeing entrepreneurship as the search for and creation of (entrepreneurial) rents. Findings: In the short to medium term the search for and creation of entrepreneurial rents give rise to supernormal profits if successful. In the longer term these rents are dissipated and accrue to society at large as cheaper and better products. Entrepreneurial rents are crucial for bringing about the innovation and continuous structural change required to generate economic growth. Practical implications: The search for entrepreneurial rents is crucial for economic development. Without the possibility to earn entrepreneurial rents, no entrepreneur would be willing to exercise entrepreneurship and exploit entrepreneurial opportunities. Successful entrepreneurship attracts imitating firms that push back profits to normal levels and the benefits of the innovation will be diffused to consumers. Social implications: Understanding the role of entrepreneurship and its compensation is crucial for analyses of potential policy measures. High ex post compensation for successful entrepreneurship cannot be taxed harshly without affecting entrepreneurs' willingness to supply effort. Originality/value: The entrepreneurial function and its compensation are often neglected in neoclassical economics. This is a major shortcoming, as the presence of and search for entrepreneurial rents are necessary for bringing about the innovation and structural change that result in economic growth.